2017
DOI: 10.1088/1361-6544/aa7f08
|View full text |Cite
|
Sign up to set email alerts
|

Stability of transition waves and positive entire solutions of Fisher-KPP equations with time and space dependence

Abstract: Abstract. This paper is concerned with the stability of transition waves and strictly positive entire solutions of random and nonlocal dispersal evolution equations of Fisher-KPP type with general time and space dependence, including time and space periodic or almost periodic dependence as special cases. We first show the existence, uniqueness, and stability of strictly positive entire solutions of such equations. Next, we show the stability of uniformly continuous transition waves connecting the unique strict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 62 publications
2
16
0
1
Order By: Relevance
“…In particular, Rawal and Shen [39] showed that the properties of positive time periodic solutions are determined by the sign of the principal spectrum point of the corresponding linearized equation of ( 8)-( 10) at the null state. We refer the reader to [40] for the study of spreading properties and traveling waves of (8) in time and space periodic case and to [42] for the study of properties of transition waves and positive entire solutions of (8) in general time and space dependence. For the study of other aspects of nonlocal dispersal models, the reader is referred to [43,48] and the references therein.…”
mentioning
confidence: 99%
“…In particular, Rawal and Shen [39] showed that the properties of positive time periodic solutions are determined by the sign of the principal spectrum point of the corresponding linearized equation of ( 8)-( 10) at the null state. We refer the reader to [40] for the study of spreading properties and traveling waves of (8) in time and space periodic case and to [42] for the study of properties of transition waves and positive entire solutions of (8) in general time and space dependence. For the study of other aspects of nonlocal dispersal models, the reader is referred to [43,48] and the references therein.…”
mentioning
confidence: 99%
“…(2) In [26], results similar to theorems 1.1 and 1.2 for the case D = R were obtained for general time dependence under the condition lim inf t−s→∞ [26] in the case when D = R and f (t, x, u) is almost periodic in t.…”
Section: Resultsmentioning
confidence: 67%
“…Lastly, even in the homogeneous space R N , non-standard transition fronts which are not invariant in any moving frame were also constructed in [24] under assumptions (1.2)-(1.5). More generally speaking, there is now a large literature devoted to transition fronts for bistable reactions in homogeneous or heterogeneous settings [6,13,18,22,48,53,60], as well as for other types of homogeneous or space/time dependent reactions in dimension 1 [16,29,30,34,35,37,40,42,43,51,52,57,58] and in higher dimensions [1,9,38,39,49,50,59,61].…”
Section: Notions Of Transition Fronts and Global Mean Speedmentioning
confidence: 99%